Investigating Holocene mountain glaciations: a plea for the supremacy of glacial geomorphology when reconstructing glacier chronologies - Winkler, Stefan (ERDKUNDE, 2018)
Investigating Holocene glacier chronologies constitutes a valuable approach within palaeoclimatic research. Recent progress of numerical dating techniques, in particular terrestrial cosmogenic nuclide dating (TCND), has given it new momentum. Highly increased precision and improved methodological procedures of data calibration seem, however, to have gradually pushed previous rigorous geomorphological analysis of the investigated glacier forelands aside. By using a well-known key site in the Southern Alps/New Zealand it is demonstrated that even alleged benchmark studies are not immune to geomorphological uncertainties. Considerable potential misinterpretations are alerting and reinforce the demand for an unaltered ‘supremacy’ of geomorphology in this context. Especially with global compilations aiming at wider palaeoclimatic conclusions critical re-assessment of glacier chronologies may occasionally seem necessary.